(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Acute ischemic stroke is the primary pathology of brain vascular system that temporarily or permanently affects brain functions as a result of ischemia. In ischemic stroke events, many biochemical and immunological reactions occur secondarily in response to the reduced cerebral blood flow. Brain tissue damage after acute ischemic stroke is mediated partly by inflammation induced by ischemia-reperfusion injury. It is thought that acute ischemic stroke due to cerebral ischemia triggers acute phase reaction and the blood concentration of ferritin and fibrinogen could rise during brain infarction. This study was carried out in the Department of Biochemistry, Sylhet MAG Osmani Medical College during the period of July 2015 to June 2016 to evaluate the status of ferritin and fibrinogen in acute ischemic stroke patients. For this study serum ferritin and plasma fibrinogen level were assessed in 50 acute ischemic stroke patients and 50 normal individuals. Data were analyzed with the help of SPSS version 19.0. Unpaired Student’s ’t’ test and Mann-Whitney U test were done to see the level of significance. Findings of the study revealed that serum ferritin and plasma fibrinogen levels were 83.1 ng/ml and 190.6 mg/dl in subjects with acute ischemic stroke, while in control subjects these were 41.3 ng/ml and 177.0 mg/dl respectively. Study showed that serum ferritin and plasma fibrinogen levels were significantly higher in patients with ischemic acute stroke compared to that of normal controls (p<0.001). It may be concluded that serum ferritin and plasma fibrinogen levels are significantly increased in acute ischemic stroke. Bangladesh J Med Biochem 2017; 10(1): 16-20